Energy Protectionism: Tren Meningkatnya Kebijakan Proteksionisme Energi di Uni Eropa - A. Mario Farrasda As; Nur Isdah Idris (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research discusses the impact of EU energy protectionism in the face of global challenges such as the Covid-19 pandemic and the energy crisis due to the Russia-Ukraine conflict. Those two major events reveal the risks of over-dependence on foreign suppliers and the lack of diversification in the EU supply chain. As a solution, the EU has implemented various policies, including RePowerE, Carbon Border Adjustment Mechanism (CBAM), and Green Deal Industrial Plan (GDIP), to reduce dependence on energy imports and increase domestic renewable energy production. Through the analysis of neoliberalism and Game Theory approaches, particularly the Prisoner's Dilemma concept, this article explores the implications of protectionist policies on international trade stability. The analysis shows that while protectionist policies can strengthen the EU's energy independence and domestic security, they also have the potential to trigger international trade tensions and protectionist retaliation from other countries.